Scalable self-supported FeNi3/Mo2C flexible paper for enhanced electromagnetic wave absorption evaluated via coaxial, waveguide and arch methods. Issue 30 (9th June 2020) - Wu, Chen; Bi, Kai; Yan, Mi
Abstract : Scalable self-supported FeNi3 /Mo2 C flexible paper with satisfactory impedance matching and multiple loss mechanisms to allow excellent wave absorption performance. Abstract : Scalable and low cost fabrication of light weight flexible electromagnetic (EM) wave absorbers is highly desirable for the rapid development of wearable electronic devices. A simple method has been developed involving incorporation of rationally designed FeNi3 /Mo2 C into cellulose fibers in the formation of thin and flexible absorbing papers with tunable electromagnetic parameters. High-performance absorption has been achieved with the minimum reflection loss (RL) reaching −51.50 dB at 13.7 GHz and an effective absorption bandwidth of 5.1 GHz with a thickness of 2.0 mm due to the synergic effects of dielectric and magnetic loss. For emerging flexible absorbers, accurate electromagnetic measurements by using a conventional coaxial method are challenging without the addition of wax or paraffin as the solidification agent. A stacking and compressing method has been developed to prepare standard-sized core samples for coaxial measurements for which the validity has been confirmed by comparison with the waveguide and arch methods. Consequently, not only a new type of effective EM absorber has been developed and verified by all the available measurement methods, but this simple and scalable method applied to fabricate flexible electronic devices is also extendable for applications in sensing, catalysis and energy storage.